2019
DOI: 10.18671/scifor.v47n123.05
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da calagem e da adubação fosfatada no crescimento inicial e na nutrição das plantas de Khaya ivorensis

Abstract: O mogno africano (Khaya ivorensis A. Chev.) é mais uma espécie florestal que vem se destacando em cultivos comerciais no Brasil. No entanto, são escassas as informações sobre a necessidade de correção da acidez do solo e da nutrição das plantas. O objetivo deste estudo foi avaliar a efeito da calagem e da adubação fosfatada nos atributos químicos do solo, no crescimento inicial e na nutrição das plantas. O delineamento experimental foi inteiramente casualizado, com seis repetições, no arranjo fatorial 2 x 5. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
1
0
2
Order By: Relevance
“…High K levels can inhibit the absorption of Ca and/or Mg, as well as high levels of these can also inhibit the absorption of K by plants. This fact is related to the antagonistic action between these cations confirmed by the increase in the K/Ca ratio, although not statistically significant (ROCHA et al, 2008). In a study to evaluate the effect of different proportions between calcium and magnesium in acidity correctives on nutrient absorption, applied to a soil with high pH buffering, by Medeiros et al (2008), they concluded that increasing proportions of Ca in relation to Mg, through the application of acidity correctives, increased the content and saturation of calcium in the cation exchange capacity (CEC) of the soil, reduced the levels of Mg and did not affect those of K.…”
Section: Ca/mg and Mg/k Ratios In Soilmentioning
confidence: 80%
“…High K levels can inhibit the absorption of Ca and/or Mg, as well as high levels of these can also inhibit the absorption of K by plants. This fact is related to the antagonistic action between these cations confirmed by the increase in the K/Ca ratio, although not statistically significant (ROCHA et al, 2008). In a study to evaluate the effect of different proportions between calcium and magnesium in acidity correctives on nutrient absorption, applied to a soil with high pH buffering, by Medeiros et al (2008), they concluded that increasing proportions of Ca in relation to Mg, through the application of acidity correctives, increased the content and saturation of calcium in the cation exchange capacity (CEC) of the soil, reduced the levels of Mg and did not affect those of K.…”
Section: Ca/mg and Mg/k Ratios In Soilmentioning
confidence: 80%
“…Esse baixo valor pode ser explicado pela forte interação que o P possui com o solo (fixação), tornando-se de forma não disponível para as plantas (Tavares et al, 2016). Mesmo comportamento também foi observado por Ros et al (2019), onde os teores de P no solo foram maiores quando foi aplicado maiores doses no cultivo de mogno-africano. Figura 3.…”
Section: Resultsunclassified
“…No entanto, se tratando de espécies secundárias como o mogno-africano, as pesquisas ainda são escassas. Na literatura alguns estudos relatam os sintomas de deficiência nutricional da cultura através de experimentos em solução nutritiva (Corcioli et al 2016;Alves et al, 2013), já outros referem à incrementos em crescimento em função de doses dos nutrientes (Vasconcelos et al 2017;Cardoso et al, 2015;Ros et al 2019). De maneira geral, os resultados destes estudos apresentaram respostas positivas no desenvolvimento da espécie, por isso, é importante a elaboração de mais estudos a fim de elevar o nível de detalhes, especialmente no uso de fontes e micronutrientes.…”
Section: Introductionunclassified